Innovations in Toroidal Propellers and Ultra-Low-Head Turbines: Applications, Performance, and Future Prospects - Subedi, Tek Raj; Shakya, Shree Raj; Bhattarai, Sudip (Journal of Engineering Issues and Solutions, 2025)
This study examines recent developments in toroidal propellers and ultra-low-head turbines for sustainable hydropower applications. Traditional turbines often face limitations in low-head environments because of reduced efficiency and the need for large infrastructure. Ultra-low-head turbines, including cross-flow, Archimedes screw, and gravitational vortex models, offer better adaptability and performance under such conditions. At the same time, toroidal propellers, with their continuous ring-like structure, reduce energy loss from tip vortices help prevent cavitation. These propellers were first used in air and marine systems but now show promise for hydropower due to their quiet and efficient operation. By reviewing findings from computer simulations, laboratory experiments, and manufacturer data, this paper explores the combined use of toroidal propellers and ultra-low-head turbines. The evidence suggests that integrating these technologies can increase efficiency and reduce environmental impacts in small-scale and decentralized systems. Future research should focus on real-world testing, improved material strength, and data-based performance monitoring. Together, these innovations may support the expansion of clean and accessible hydropower in both developed and developing regions.